Gaya Bahasa dalam Lirik Lagu "Satu Bulan", "Apa Mungkin" dan "Terlintas" pada Album "Terlintas" karya Bernadya - Zakira, Raihana (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2025)
The music industry is currently thriving with new songs popularized by young musicians. One striking example is Bernadya's Terlintas album, which presents a number of popular songs thanks to its lyrics that attract listeners' attention. This study aims to analyze the use of language styles in the lyrics of the songs on Terlintas album and explore the meaning contained in them. The three songs studied in this research are â€œSatu Bulanâ€, â€œApa Mungkinâ€, and â€œTerlintasâ€. Using a descriptive qualitative approach, this study collected data through listening and note-taking techniques. The data obtained from the song lyrics were then analyzed using Keraf's (2006) stylistic theory, which distinguishes stylistic language based on direct and indirect meaning. The results show that there are three types of dominant language styles in the song lyrics, namely comparison, affirmation, and figurative language styles. Comparative language style is seen through the use of figures of speech such as metaphor, hyperbole, personification, and symbolism, which function to enrich meaning and create new images for listeners. Meanwhile, oppositional language style appears in the form of subtle criticism through irony and allusion. This research confirms that the use of language styles in song lyrics has an important role in exploring deeper meanings and strengthening the emotional message that the songwriter wants to convey. Therefore, song lyrics not only function as a means of entertainment, but also as a medium to convey ideas and feelings in a more complex manner.